Findings from the Myanmar Agriculture Policy Support Activity contribute to decision on USD 430M loan program to farmers by Myanmar Agriculture Development Bank - CGIAR Research Program on Policies, Institutions, and Markets (2021)
A USAID factsheet on the Myanmar Agriculture Policy Support Activity published in 2022 lists the Myanmar Agriculture Development Bank loan program among the results of this PIM-supported activity.